The impact of Herdsmen Activities on farmers' safety and food security in Anambra State Nigeria (2017 – 2022) - Okoye Emmanuel Chinedu; Anaekwe Victor Benjamine; Okechukwu Ozioma Hossan (Paspama Institute, 2025)
The purpose of this study is to asses impact of herdsmen Activities on farmers' safety and food security in Anambra State Nigeria. To that effect, two research questions and two hypotheses were formulated to guide the study, The objectives of the research work were to determinethe effect of the herdsmen activities on the social of lives and properties, of the people living in Anambra State. The study made use of frustration-aggression theory as the theory that supports the study. The study adopted cross-sectional survey research design, while data were gathered from primary and secondary sources, Structured questionnaire was developed and used for data collection from a sample size of 323 respondents, that where gotten through the use of the taro Yamane formula, The respondents are made up of farmers and the members of the selected local government area in Anambra State, purposive sampling Technique was used to administer the questionnaires, while Chi-square test was used to test the hypothesis formulated for the study. The outcome of the analysis carried out shows that the herders farmers clashes affect the social life of the people living in Anambra state. However, the study recommends that the security agents need to Sustain and build on the existing success recorded so far, by being more proactive than reactive, the government needs to also sensitize the members of the general public on the new anti-grazing laws, and compensate those who have been traumatized. the government needs to bring to light the success recorded so far in the cause of arresting the herders-farmers clashes in the state, they also need to orientate and sensitize the farmers and the general public of the state, on the need to return to normalcy our reputable attribute of been peaceful and hospitable